The performance of a combination of heparin-binding protein with other biomarkers for sepsis diagnosis: an observational cohort study - Liwei Feng; Shujie Liu; Jieying Wang; Yan Gao; Fengjie Xie; Jianguo Gong; Sheng Bi; Zhipeng Yao; Yue Li; Wenhua Liu; Chunming Guan; Ming Zhang; et al. (BMC Infectious Diseases, 2024)
Abstract Background HBP, a novel biomarker released from neutrophils, may induce inflammatory responses and exacerbate vascular permeability, representing the pathophysiological characteristics of sepsis and septic shock. However, it remains uncertain whether the combination of HBP with other biomarkers yields enhanced diagnostic capacity for sepsis. We hypothesized that measurements included IL-6·IL-8·HBP, IL-6·IL-8·HBP/ALB and HBP/ALB which based on HBP will improve its diagnostic efficacy and even better than the traditional infection biomarkers. Methods Between July 2021 and June 2022, we carried out a comprehensive, multi-center, observational cohort study spanning six leading tertiary hospitals located in Heilongjiang Province, China. Patients were stratified into three categories based on the severity of infection: non-sepsis, sepsis, and septic shock. We collected clinical and laboratory data, along with infection and inflammation biomarkers, for analysis. Results A total of 195 patients were enrolled. Among the three groups, patients with septic shock (n = 75, 38.5%) had significantly higher baseline levels of HBP, WBC, Lac, CRP, PCT, IL-6, IL-8, and IL-10 compared to non-sepsis patients (n = 43, 22.0%) and sepsis patients (n = 77, 39.5%), with statistically significant differences (p < 0.05) observed for all parameters. When compared to SOFA score and traditional markers of CRP, PCT, IL-6 and IL-8, the combined indexes of IL-6·IL-8·HBP and IL-6·IL-8·HBP/ALB demonstrated significantly improved diagnostic performance for sepsis and septic shock (AUC 0.911 and 0.902 respectively, p < 0.001). Conclusions The combined measurements of IL-6·IL-8·HBP and IL-6·IL-8·HBP/ALB can augment the diagnostic capacity of HBP for sepsis, and offer reliable early supplementary indicators to traditional biomarkers for assessing disease severity in patients with infection.